Layanan Khusus Keagamaan di RA Lisda sebagai Bentuk Implementasi Manajemen Pendidikan - Rizqia, Shofia Zahra; Sianturi, Risbon; Quds, Dhiya El (AS-SABIQUN, 2023)
Education is an important aspect to prepare a quality generation of the nation. Of course, in education there needs to be good educational management in order to achieve success in educational goals. However, the management of education at educational institutions in Indonesia is still far from good. The aim of this research is to find out about education management and the implementation of special services in formal early childhood education institutions, namely RA. This research uses descriptive qualitative methods. Researchers conducted research at RA LISDA targeting RA LISDA school principals, as well as carrying out documentation for data collection. Then the researcher carried out data reduction to analyze the data, present the data, and draw conclusions. The results of this research are that RA LISDA has implemented education management well and provided special religious services as a form of implementation of education management. This special religious service aims to shape the morals and behavior of students to become human beings who always obey Allah SWT. However, RA LISDA has not yet fully and completely provided special services, because there is no specific and permanent program.